Considering the Lessons of Curriculum Studies in the Design of Science Instruction: Varieties of Meaning and Implications for Teaching and Learning - William F. McComas (MDPI AG, 2024)
This article is an introduction to the rich domain of curriculum studies with specific reference to science teaching and learning. It is designed not as a systematic review or theoretical treatise but rather as an overview for those charged with transforming science content and processes into a classroom curriculum. In other words, while written from the scholarly perspective of curriculum studies, the hope is that it will be seen by teachers as a set of possibilities rather than recommendations while reminding educators that what happens in classrooms to students and their parents is the curriculum, but it is only one of many that might have been delivered. To accomplish this, this paper explores the complex definition of curriculum including the notions of the kinds of curriculum from null, to formal, received, and learned with an emphasis on what occurs as a specific curriculum design results in effective and even faulty learning, a unique consequence proposed here. Next, we explore the common curriculum ideologies or orientations including those focused on academic advancement, tradition, student-centeredness, and social improvement. Finally, a formal recommendation for the content of science instruction in the U.S.-the Next-Generation Science Standards, is are considered as a conclusion by applying the expansive perspective of the term and nature of curriculum discussed throughout.